Anticoagulation Management and Heparin Resistance During Cardiopulmonary Bypass: A Survey of Society of Cardiovascular Anesthesiologists Members. (August 2019) - Sniecinski, Roman M.; Bennett-Guerrero, Elliott; Shore-Lesserson, Linda
Abstract : We surveyed Society of Cardiovascular Anesthesiologists members regarding anticoagulation practices for cardiopulmonary bypass and attitudes on heparin resistance. Of 550 respondents (18.5% response rate), 74.9% (95% CI, 71.3%–78.5%) used empiric weight-based dosing of heparin, and 70.7% (95% CI, 66.9%–74.5%) targeted an activated clotting time of either 400 or 480 seconds to initiate cardiopulmonary bypass. Of note, 17.1% (95% CI, 13.9%–20.2%) of respondents reported activated clotting time targets lower than those recommended by recent 2018 Society of Thoracic Surgeons/Society of Cardiovascular Anesthesiologists/American Society of Extracorporeal Technology guidelines or failed to monitor heparin effects at all. When heparin resistance was encountered, 54.2% of respondents (95% CI, 50.0%–58.4%) administered antithrombin concentrates as a first-line therapy.